Antimotility, anti-diarrheal, and antibacterial activities of hydroalcoholic extract of Cordia dichotoma leaves in Wistar rat - Rahul Dev; Nrip Kishore Pankaj; Lenesha Manhas; Pawan Kr. Verma; Amruthanand; Thakur Uttam Singh; Neelesh Sharma (The Indian Veterinary Journal, 2025)
activities of the hydro-alcoholic extract of Cordia dichotoma leaves (CD). The CD was screened on the dose-response curve (DRC) of acetylcholine (Ach) over isolated ileum. CD was evaluated in the model (n=6), including Group I received 0.1% Carboxymethyl cellulose@1ml/100g b.wt., Group II, Loperamide@2.5mg/Kg b.wt., Group III, IV, and V, had CD@125, 250, and 500mg/Kg respectively. The CD was also screened for its antibacterial effects over Escherichia coli and Staphylococcus aureus.CD shifted the DRC of Ach towards the right, showed a dose-dependent decline in diarrhea, and had antibacterial activities over E. coli.